Prayers at Dawn, Fuji at Noon: Music, Spirituality and Everyday Wellbeing among Urban Informal Workers in Ibadan - ADEJUBE, Samuel Ayoola (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study examines how music and spirituality shape everyday wellbeing among urban informal workers in Ibadan, Nigeria. In a context where market traders and motor park drivers navigate long and unpredictable workdays, auditory practices play a crucial role in regulating mood, fostering resilience, and facilitating social interaction. Despite the centrality of music and spiritual engagement in daily life, little is known about how these practices are structured and experienced across time, creating a gap in scholarship on the intersection between musicology and African urban soundscapes. Using qualitative methods, including in-depth interviews with 20 participants and non-participant observation in selected markets and motor parks, the study traces a temporal shift in sonic environments. On one hand, mornings are dominated by gospel songs, communal prayers, and exhortations with repetitive melodic and rhythmic structures that provide moral grounding, optimism, and group cohesion. On the other hand, afternoons shift to secular genres such as fuji, highlife, and afrobeats, whose polyrhythms, call-and-response motifs, and cyclical grooves sustain energy, encourage social interaction, and support coping with the demands of urban labour. Findings reveal that workers deliberately curate sacred and secular sounds to navigate both economic and social pressures, promoting personal and collective wellbeing. By situating music at the intersection of spirituality, work, and resilience, the study highlights how auditory practices function as both social and affective resources. This research contributes to African urban ethnomusicology by demonstrating the structural and emotional dimensions of music in everyday life, and its quotidian role in shaping individual and communal resilience.